Genome sequence of the clover symbiont Rhizobium leguminosarum bv. trifolii strain CC275e. Issue 1 (December 2015) - Delestre, Clément; Laugraud, Aurélie; Ridgway, Hayley; Ronson, Clive; O'Callaghan, Maureen; Barrett, Brent; Ballard, Ross; Griffiths, Andrew; Young, Sandra; Blond, Celine; Gerard, Emily; Wakelin, Steve
Abstract Rhizobium leguminosarum bv.trifolii strain CC275e is a highly effective, N2 -fixing microsymbiont of white clover (Trifolium repens L.). The bacterium has been widely used in both Australia and New Zealand as a clover seed inoculant and, as such, has delivered the equivalent of millions of dollars of nitrogen into these pastoral systems.R. leguminosarum strain CC275e is a rod-shaped, motile, Gram-negative, non-spore forming bacterium. The genome was sequenced on an Illumina MiSeq instrument using a 2 × 150 bp paired end library and assembled into 29 scaffolds. The genome size is 7, 077, 367 nucleotides, with a GC content of 60.9 %. The final, high-quality draft genome contains 6693 protein coding genes, close to 85 % of which were assigned to COG categories. This Whole Genome Shotgun project has been deposited at DDBJ/EMBL/GenBank under the accession JRXL00000000. The sequencing of this genome will enable identification of genetic traits associated with host compatibility and high N2 fixation characteristics inRhizobium leguminosarum. The sequence will also be useful for development of strain-specific markers to assess factors associated with environmental fitness, competiveness for host nodule occupancy, and survival on legume seeds (New Zealand Ministry of Business, Innovation and Employment program, 'Improving forage legume-rhizobia performance' contract C10X1308 and DairyNZ Ltd.).